Expressing our passion in leadership. Issue 3 (16th April 2023) - Skipworth, Stan
Abstract : As another school year ends, we may find ourselves taking note of and expressing our sentiments and feelings for others more deliberately. I find myself considering the unique form of passion that leaders have for their teams and team members. Passion is indeed a tremendously powerful element in any relationship, but the passion that is expressed through a leader's professional actions is something that has both a lasting and influential effect upon those whom the leader serves.